SWOT ANALYSIS FOR SUSTAINABEL INTEGRATED ECOTOURISM DEVELOPMENT SEBRANG FISHING VILLAGE, BELAWAN 1 MEDAN - Effendy, Yusen (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study aimed to analyze the potential for sustainable integrated ecotourism development in Sebrang Fishing Village, located in Belawan 1 Village, Medan City, North Sumatra Province, Indonesia. Drawing on the SWOT method, the research examined the socio-economic and environmental conditions of the village, as well as its cultural heritage, to identify opportunities and challenges for ecotourism development. The findings revealed various strengths, weaknesses, opportunities, and threats (SWOT) impacting the village's tourism potential. Strengths include unique coastal stilt houses and community cohesion, while weaknesses encompass dilapidated infrastructure and limited financial resources. Opportunities lie in leveraging cultural heritage and environmental assets, while threats include environmental degradation and socio-economic vulnerabilities. Based on the analysis, recommendations are proposed to enhance strengths, address weaknesses, capitalize on opportunities, and mitigate threats, facilitating the sustainable development of ecotourism in Sebrang Fishing Village.